Effectiveness of Teamwork Excellence Training: A Case Study at PT ICI Manado - Djuuna, Meykel; Danang, Surya; Jusuf, Sabrun (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to improve team performance at PT. Insan Cerdas Indonesia (ICI), Ranotana Branch, through a psychological intervention in the form of the